Isolation and analysis of peptidic fragments of alpha-gliadin using reversed-phase high-performance liquid chromatography - Kocna, P; Fric, P; Kocová-Holáková, M; Slabý, J; Kasafírek, E; Hekkens, W T (Journal of chromatography, 1988)
Peptidic fragments of alpha-gliadin were obtained by peptic-tryptic-pancreatic (PTP) digestion of the alpha-gliadin fraction isolated by ion-exchange chromatography on a sulphopropyl-Sephadex C-50 column. The proteolytic digest was fractionated by ultrafiltration into three subfractions, PTPa1-PTPa3. The subfraction PTPa2 was then analysed and individual peaks were separated using reversed-phase high-performance liquid chromatography (RP-HPLC) using a gradient of acetonitrile in 0.1% trifluoroacetic acid and a Separon SGX-C18 sorbent. A 100-mg amount of the PTPa2 subfraction was separated in a single analysis by preparative RP-HPLC and twenty peaks were obtained for further characterization. The molecular mass in range 300-3000 was established for individual peptidic fragments by gel-permeation chromatography on a TSK-G2000 SW column.
Keywords: ektroforéza na škrobovém gelu; Plant Proteins; peptidové fragmenty; Chromatography, High Pressure Liquid; Electrophoresis, Starch Gel; Peptide Fragments; gliadin; rostlinné proteiny; vysokoúčinná kapalinová chromatografie; Gliadin